Company-Specific Factors and Determination of Target Firms in Mergers and Acquisitions Deals: Experience from Emerging Markets : Array - Okofo-Dartey, Emmanuel (Acta Universitatis Danubius. Œconomica, 2021)
This study investigates firm-specific variables that motivate acquirers to pursue target firms from the emerging markets in mergers and acquisitions transactions. Firms from the emerging markets continue to serve as targets instead of acquirers in acquisitions deals. However, this trend appears to be changing since some firms from the emerging markets are becoming more active in M & A deals as acquirers. Several factors may account for the interest various acquirers show in pursuing targets from the emerging markets. These factors could include the company-specific factors or variables of these targets. Using 154 firms gleaned from the Bloomberg database from 2007 to 2017 on ten (10) emerging market countries, the study employs the logistic regression technique to explore the likely firm-specific variables of emerging market targets that influence acquirer firms to be interested in emerging markets firms as targets in M&A transactions. We find that financial leverage, market-to-book ratio, and the ratio of cash and equivalent to total assets of the target firms are more likely to influence the acquirers' decisions to pursue these firms as targets. In contrast, total assets and sales growth of these targets are less likely to motivate acquirers to become interested in these firms as M&A targets. Finally, return on assets (showing profitability levels) does not influence the acquirers’ decisions. Our findings have implications for regulation and policy development to support investment decisions of potential acquirers and other investors interested in emerging market firms.